Eskatologi Hamâmî Zâdah: Kajian Atas Kitab Tafsîr Sûrah Yâsin - Husna, Rifqatul; Somad, Abd. (Fakultas Ushuluddin dan Humaniora UIN Antasari Banjarmasin, 2022)
It is well known that in Surah Yâsin, there are several discussions, one of which is the discussion on eschatology. This research was conducted to make it easier to know and review the eschatology in surah Yâsin. The researcher chose Hamâmî Zâdah as the object of his book entitled Tafsîr Surah Yâsin because he is a modern Muslim scholar (12 H.) who has talked a lot about eschatology, but not much is highlighted it. This study uses a qualitative method with a descriptive-analytic approach, which in the end, the researcher can conclude that the eschatological points in the Interpretation of Surah Yâsin written by Hamâmî Zâdah include; blowing of the trumpet, resurrection after death, mahshar, hisâb, handing over of charity books, mîzân, shirath, heaven, hell and the existence (condition) of people who are in heaven or hell. This study of eschatology serves as material for reflection on the metaphysics of the afterlife and motivation and education for all of us to live a better life and adequately prepare for the next life.